PENERAPAN THEORY OF CONSTRAINT (TOC) UNTUK MENINGKATKAN PROFITABILITAS PADA PERUSAHAAN BAKPIA LATIEF DI KOTA KEDIRI - Syuraika, Eky; Ratih, Nur Rahmanti (Jurnal Ilmiah Cendekia Akuntansi, 2019)
The development of the food business is one of them in the city of Kediri. which is in the province of East Java where the food business from year to year is growing. One of them is the Pia Latief Kediri company. The high market demand must certainly be balanced with the speed of the company in producing a product without reducing the quality and quality produced. One method that can be used to increase the speed of production is the Theory of Constraint. The purpose of this study was to determine and analyze the application of the Theory of Constraint (TOC) to increase the profitability of the Bakpia Latief company in Kediri. The data analysis technique used in this study is to identify increasing constraints, determine the most profitable product composition, maximize the flow through existing constraints, calculate margin throughput and calculate profitability. Before the implementation of the TOC, there was a lack of time available to meet the demand for bakpia, so that the demand for bakpia in the amount of 3,345,000 boxes for dry bakpia and 850,000 boxes for wet bakpia was threatened to be inappropriate. After applying the theory of constraints, this can be overcome by applying time with takt time so that the available time can be used in the production process, which in turn all requests both dry bakpia products and wet bakpia can be fulfilled. in wet bakpia products, while in dry bakpia products amounted to Rp. 22,537,500,000, the total throughput was Rp. 25,087,500,000. Profitability of companies proxied by NPM was 56.81%. It is expected that by applying the theory of constraints can help companies in identifying the constraints that exist in the company, especially in the production section and can provide alternative solutions to problems in overcoming obstacles. It is better for the company to make a more scheduled ordering system and product production system in accordance with the existing capacity to avoid capacity inequality